Cultivating Teacher Resilience International Approaches, Applications and Impact - Mansfield, Caroline F. (Springer Nature, 2020)
This open access book follows the development of the Building Resilience in Teacher Education (BRiTE) project across Australia and internationally. Drawing on the success of this project and the related research collaborations that have since emerged, it highlights the importance of cultivating resilience at various stages of teachers' careers. Divided into three sections, the book includes conceptual, empirical and applied chapters, designed to introduce readers to the field of research, provide empirical evidence and showcase innovative applications. The respective chapters illustrate the ways in which teacher resilience can be enhanced in a variety of contexts, and address specific learning activities, case studies, resources and strategies, student feedback and applied outcomes. They also consider future directions including cross-cultural applications and the use of technologies such as augmented reality. The book will appeal to researchers, teacher educators and teachers, as well as those interested in supporting the cultivation and ongoing development of professional resilience for pre-service and practicing teachers.